2013
DOI: 10.1590/s0103-21002013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Revascularização miocárdica: estratégias para o enfrentamento da doença e do processo cirúrgico

Abstract: Objective: Knowing the strategies used by patients in coping with coronary heart disease and myocardial revascularization surgical procedure. Methods: The Grounded Theory method was used as a methodological framework for the reading of data from a larger study entitled: Contextualizing the surgical experience and the living process of the patient undergoing myocardial revascularization. Data collection was conducted from October 2010 to August 2011, through semi-structured interviews with three sample groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 6 publications
(7 reference statements)
0
5
0
16
Order By: Relevance
“…Other researches with qualitative approaches demonstrated the presence of positive feelings and the pursuit of faith and hope in religiosity when facing the event of cardiac surgery, with high values of spiritual resources in the confrontation with the operation (14)(15) . One more cohort study observed 335 patients submitted to cardiac surgery, excluding the ones of emergency and heart transplant, for 30 months and concluded more than the religiosity implication in reducing preoperative anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…Other researches with qualitative approaches demonstrated the presence of positive feelings and the pursuit of faith and hope in religiosity when facing the event of cardiac surgery, with high values of spiritual resources in the confrontation with the operation (14)(15) . One more cohort study observed 335 patients submitted to cardiac surgery, excluding the ones of emergency and heart transplant, for 30 months and concluded more than the religiosity implication in reducing preoperative anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%
“…This study 12 also pointed out that there is a dependency after the surgical procedure of the patients with the caregiver team who, in order to be released from this after discharge, had to support their relatives, while the minority mentioned that of their friends. In another study 13 in Santa Catarina, at the Specialized Center of Cardiology, addressing as subjects of the study, the narrators, patients submitted to MCR, their relatives and the professionals involved in intensive care, points out that the patient, in face of their fragility after the CC, seeks safety and support in the family in order to rely on this environment in the face of the unknown situation.…”
Section: Took a Weight Off My Back It Was A Divine Gift Which mentioning
confidence: 99%
“…A família, como grupo, é corresponsável pela saúde e bem-estar dos seus membros (4) e em um processo de doença pode tornar-se aliada dos profissionais de saúde colaborando para a recuperação da saúde (15). Para a pessoa que está debilitada e em sofrimento, sobretudo no pós IAM imediato, devido à dificuldade de realizar as atividades autonomamente, receber atenção e carinho por meio da presença possibilita a interação entre os envolvidos.…”
Section: Discussaõ E Conclusãounclassified